ANALYSIS OF SUSTAINABLE INFRASTRUCTURE ENHANCEMENT IN EDUCATION INSTITUTIONS - N, NISCHAY (Digital Repository of Theses, 2023)
The UN Global Commission on Environment with Development defines sustainability as meeting present needs without hindering future generations from meeting their own needs. It involves ensuring equitable sharing of resources, generating profits, and maintaining an environment that supports health, productivity, and cultural life. Sustainable development fosters economic prosperity and preserves the environment and limited resources. It also emphasizes providing essential educational facilities to meet student demands. Green management (GM) refers to environmentally responsible organizational practices, which enhance health, comfort, and productivity for workers. GM guidelines improve building performance, as noted by PAEVERE and BROWN. Sustainability and GM aim to utilize and maintain infrastructure in an environmentally friendly manner. Research methodology of design, The survey focuses on the performance of an education facility as the dependent variable. Independent variables were divided into sections in the questionnaire, specifically addressing demographic status and factors such as familiarity with the concept and perceptions of sustainable buildings. Both a control group and an experimental group were utilized. The control group design did not involve a comparison. Raven's Progressive Matrices indicated similar intellectual abilities in both the control and experimental groups. Quasi-experimental designs do not involve random sampling or random assignment of participants to groups. Data collection process, the data were analyzed using IBM-SPSS, version 2. Factor analysis was conducted on 32 observed variables using Principal Component Analysis (PCA) to determine the impact of independent variables on the dependent variable. The dataset met the necessary prerequisites and assumptions for using this tool. A total of 164 university instructors, 122 postgraduate students in the built environment, and 114 in-house building specialists contributed to the study. T-Test Analysis was employed to assess the significance of factors, which revealed barriers to utilizing sustainability and GM principles for achieving objectives. Correlation and regression analyses were conducted to test the hypotheses, indicating that sustainability and GM have a positive impact on educational facilities. The research examines sustainability and GM as effective solutions for improving educational facility performance and overcoming obstacles in India. Stakeholders play crucial roles in achieving a significant turnaround in the education sector. Despite poor infrastructure, there is a growing concern for quality education, particularly in southern India. To replicate the success of Indian scholars and elevate universities globally, sustainable education facility development should be embraced. This paradigm shift requires immediate recognition from stakeholders and a departure from traditional methods of building infrastructure.